2007
DOI: 10.1016/j.jacc.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Initiation and Withdrawal of Cardiac Resynchronization Therapy on Papillary Muscle Dyssynchrony and Mitral Regurgitation

Abstract: Cardiac resynchronization therapy can acutely reduce MR in patients with dyssynchrony involving the papillary muscles; interruption of CRT at 6 months' follow-up, however, resulted in acute loss of resynchronization with recurrence of MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 35 publications
5
96
0
3
Order By: Relevance
“…One-year mortality was not reported, although the small study size did not allow for meaningful assessment of survival. Data are not provided on the use of evidence-based medical therapies in either the study by Chan et al 22 or the study by Fattouch et al, 21 including on the use of cardiac resynchronization therapy when appropriate, an intervention proven to reduce the severity of ischemic MR. [23][24][25] Firm conclusions regarding the efficacy and safety of MVRp at time of CABG surgery in patients with moderate ischemic MR cannot be drawn from these studies. Nevertheless, and despite the several important limitations and concerns noted, both groups of investigators are to be congratulated for conducting these RCTs.…”
Section: Article See P 2502mentioning
confidence: 99%
“…One-year mortality was not reported, although the small study size did not allow for meaningful assessment of survival. Data are not provided on the use of evidence-based medical therapies in either the study by Chan et al 22 or the study by Fattouch et al, 21 including on the use of cardiac resynchronization therapy when appropriate, an intervention proven to reduce the severity of ischemic MR. [23][24][25] Firm conclusions regarding the efficacy and safety of MVRp at time of CABG surgery in patients with moderate ischemic MR cannot be drawn from these studies. Nevertheless, and despite the several important limitations and concerns noted, both groups of investigators are to be congratulated for conducting these RCTs.…”
Section: Article See P 2502mentioning
confidence: 99%
“…51 The beneficial effect of CRT on sec ondary MR occurs through the reversal of adverse LV remodelling, improved LV systolic function, increased closing force (indicated by a change in EROA, which was directly related to the increase in LV dP/dt) and improved coordinated timing of mechanical activation of the papillary muscles. 52,53 However, these bene fits are reversible, and studies have demonstrated that CRT withdrawal after 6 months of implantation acutely results in MR recurrence. 54,55 In addition, owing to the smaller benefits in LV remodelling derived from CRT in patients with ischaemic cardiomyopathy, the regression of MR is subsequently less in this subset of patients.…”
Section: Cardiac Resynchronization Therapymentioning
confidence: 99%
“…CRT reduces the amount of FMR in patients with LV systolic failure (9)(10)(11)(12)(13)(14)(33)(34)(35)(36)(37)(38). Effects of CRT on FMR are acute and longterm, due to the reverse remodeling of the LV.…”
Section: Cardiac Resynchronization Therapy and Functional Mitral Regumentioning
confidence: 99%
“…CRT reduces the amount of FMR in patients with left ventricular (LV) systolic failure (9)(10)(11)(12)(13)(14). Studies have shown that the severity of FMR was correlated with the papillary muscle dyssynchrony (PMD) (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%